THEORETICAL ANALYSIS OF TEMPERATURE DISTRIBUTION IN FRICTION STIR WELDING (Journal of Engineering, 2011)
Friction stir welding (FSW) is a relatively new welding process that may have significantadvantages compared to the fusion processes as follow: joining of conventionally non-fusionweldable alloys, reduced distortion and improved mechanical properties of weldable alloysjoints due to the pure solid-state joining of metals. In this paper, a two-dimensional modelbased on finite element analysis is used to study the thermal history and thermomechanicalprocess in the butt-welding of aluminum alloys. The model incorporates the mechanicalreaction of the tool and thermomechanical process of the welded material. The heat sourceincorporated in the model involves the friction between the material and the probe and theshoulder. The calculation result also shows that preheat to the workpiece before process isbeneficial to FSW. The effects of welding parameters such as preheating (100, 200) °C,rotational speed (960, 1200) rpm and linear speed (110, 155, 195) mm/min on the distributionof temperature of Al Alloy will be studied.